Napływ bezpośrednich inwestycji zagranicznych do Polski w latach 2003-2004 ze szczególnym uwzględnieniem inwestycji ze Stanów Zjednoczonych - Jankowiak, Anna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The Polish economy, in order to prosper, needs a flow of foreign direct investments (FDI). The course of inflow of FDI to Poland was initiated after political transformation and reached the highest level in the late ninety's and in the year 2000. Polish government predicts that also in the year 2006, the intensity of foreign direct investments will amount to 10 billion dollars. This outlook seems real for the sake of Poland ranked on the second position among Central and Eastern European countries in FDI in 2004. Due to globalization processes, investors are looking for countries which offer them better conditions to do business. Lower wages and Corporate Income Taxes (CIT) draw foreign investors, which is why year by year Poland is becoming a more attractive place on the map to locate business. The majority of the foreign capital was invested in Poland by 15 EU countries but American and Asian investors also played an important role. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1173, s. 150-159